2015
DOI: 10.33772/djitm.v5i2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Circulating Fan and Natural Ventilation on the Thermal Comfort Performance in a Building in Southeast Sulawesi

Abstract: The unbalance on the supply and demand on the energy has an impact on the escalating energy price and potentially impedes the development. One of the power demands comes from the energy utilization in the building sector, in which the cooling system is among them. The application of the air conditioning based on the refrigerator system is obviously consuming much energy in the building. Thus reducing the role of this power consumed cooling system is so imperative. To apply the circulating fan or to employ the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The primary function is to remove the excess indoor heat and accelerate the convection process and evaporative cooling. Results of the ventilation study in tropical buildings have demonstrated that mechanical ventilation can improve indoor thermal conditions, whether complimentary or the sole strategy [5]. Mechanical ventilation can induce air velocity, which is very beneficial from the standpoint of physiological cooling [17].…”
Section: Ventilation Strategy In Buildingmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary function is to remove the excess indoor heat and accelerate the convection process and evaporative cooling. Results of the ventilation study in tropical buildings have demonstrated that mechanical ventilation can improve indoor thermal conditions, whether complimentary or the sole strategy [5]. Mechanical ventilation can induce air velocity, which is very beneficial from the standpoint of physiological cooling [17].…”
Section: Ventilation Strategy In Buildingmentioning
confidence: 99%
“…Previous studies stated that natural ventilation should be encouraged in tropical housing if the objective is to limit energy consumption and operating cost [3,4]. Yet other studies also indicate that natural ventilation alone is insufficient [5]. These arguments owe to the fact that wind condition varies over time, and architectural features tend to be fixed or less flexible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation